Role of Graphene in Constructing Multilayer Plasmonic SERS Substrate with Graphene/AgNPs as Chemical Mechanism—Electromagnetic Mechanism Unit - Liu, Lu (Nanomaterials (Basel), 2020)
Graphene–metal substrates have received widespread attention due to their superior surface-enhanced Raman scattering (SERS) performance. The strong coupling between graphene and metal particles can greatly improve the SERS performance and thus broaden the application fields. The way in which to make full use of the synergistic effect of the hybrid is still a key issue to improve SERS activity and stability. Here, we used graphene as a chemical mechanism (CM) layer and Ag nanoparticles (AgNPs) as an electromagnetic mechanism (EM) layer, forming a CM–EM unit and constructing a multi-layer hybrid structure as a SERS substrate. The improved SERS performance of the multilayer nanostructure was investigated experimentally and in theory. We demonstrated that the Raman enhancement effect increased as the number of CM–EM units increased, remaining nearly unchanged when the CM–EM unit was more than four. The limit of detection was down to 10(−14) M for rhodamine 6G (R6G) and 10(−12) M for crystal violet (CV), which confirmed the ultrahigh sensitivity of the multilayer SERS substrate. Furthermore, we investigated the reproducibility and thermal stability of the proposed multilayer SERS substrate. On the basis of these promising results, the development of new materials and novel methods for high performance sensing and biosensing applications will be promoted.